PENGHITUNG DAN PEMBATAS DAYA LISTRIK PADA KAMAR KOS BERBASIS MIKROKONTROLER - , MUHAMMAD FARHAN AMRULLOH ([Yogyakarta] : Universitas Gadjah Mada, 2014)
In realizing the power counter and strip on boarding room based microcontroller there have parts of hardware which needed are power supply current sensor unit, voltage sensor unit, LCD viewer unit, and driver relay unit to be combined become asystem. Part of software was desigred using C language with IDE Arduino programme as the compiler. The power counter and strip on boarding room based microcontroller consists of there major circuit are input, processors, and output. The input consists of current sensor circuit, and voltage sensor circuit. The processors consists of the minimum system of ATmega328 (Arduino). The output consists of viewer form LCD text 16x2 and relay. The power strip software on boarding room based microcontroller consists of some part: iclusion function, LCD port definition, ADC mode, variable declaration and function.